Computational Study of E-Compound from the Vitex Family as Novel Potential Anti-Alzheimer Agents: An in Silico Study - Syahputra, Hariyadi Dharmawan; Nasri, Nasri; Kaban, Vera Estefania (CV. Nusantara Scientific Medical, 2025)
The degenerative disease of memory that most attacks the frontal lobe is Alzheimer's. Therapy for Alzheimer's is mostly done by targeting an increase in the amount of acetylcholinesterase in the synapse cleft by inhibiting the enzyme acetylcholinesterase. The purpose of this study is to conduct a comparative study of vitexifolin E compounds from the vitexium plant family with donepezil to obtain more precise and targeted drug candidates in Alzheimer's therapy. The results showed that donepezil compounds have a more active probability (0.53) of being carcinogenic compared to vitexifolin E with the web-based application Protox II. Tests with in silico studies found that the hydrogen bonding results of vitexifolin E had values close to those of donepezil drugs, as well as RMSD results with receptors between donepezil and vitexifolin E (1,781; 1,281) and free energy obtained (-6.9; -7.8). Based on these results, it can be concluded that vitexifolin E compounds can have good enough potential to be developed in implementing the treatment of Alzheimer's disease therapy.